Lung Delivery of Indacaterol and Mometasone Furoate Following Inhalation of QMF149 in Healthy Volunteers. Issue 4 (22nd January 2016) - Vaidya, Soniya S.; Khindri, Sanjeev; Maahs, Suzanne; Machineni, Surendra; Hara, Hisanori; Juan, Axel; Kaiser, Günther
Abstract: This single‐dose, 4‐period crossover study evaluated the pharmacokinetics (PK) of the β2 ‐agonist indacaterol maleate and the corticosteroid mometasone furoate (MF) after inhalation of a fixed‐dose combination (QMF149, indacaterol maleate/MF, 500/400 μg) via the Twisthaler (TH) device with and without activated charcoal and postdose mouth rinsing in healthy volunteers. The PK of indacaterol maleate 300 μg inhaled via the Breezhaler (BRZ) device was also characterized. Relative bioavailability of indacaterol and MF for inhalation with versus without charcoal, based on AUClast, was 0.25 (90% confidence interval [CI], 0.18–0.35) and 0.70 (90%CI, 0.52–0.93), respectively. Thus, 25% and 70% of systemic exposure of indacaterol and MF, respectively was due to pulmonary absorption and 75% and 30%, respectively, was due to gastrointestinal absorption. Mouth rinsing reduced the systemic exposure of indacaterol by approximately 35% but had no relevant effect on the exposure of MF. Dose‐normalized AUClast for indacaterol inhaled via the BRZ device was 2.3‐fold higher than QMF149 via the TH device. All treatments had a good safety profile and were well tolerated. Data from this study and comparison with inhalation of indacaterol via the BRZ device suggest that the latter was more efficient than the TH device regarding lung delivery of indacaterol.